Recent advances in the development of biocompatible nanocarriers and their cancer cell targeting efficiency in photodynamic therapy - Dhilip Kumar, Sathish Sundar; Abrahamse, Heidi (Frontiers in Chemistry, 2022)
In recent years, the role of biocompatible nanocarriers (BNs) and their cancer cell targeting efficiency in photodynamic therapy (PDT) holds potential benefits for cancer treatment. Biocompatible and biodegradable nanoparticles are successfully used as carrier molecules to deliver cancer drugs and photosensitizers due to their material safety in the drug delivery system. Biocompatible nanocarriers are non-toxic and ensure high-level biocompatibility with blood, cells, and physiological conditions. The physicochemical properties of BNs often enable them to modify their surface chemistry, which makes conjugating specific ligands or antibodies to achieve cancer cell targeting drug delivery in PDT. This review article focuses on the various types of BNs used in targeted drug delivery, physicochemical properties, and surface chemistry of BNs in targeted drug delivery, advantages of BNs in drug delivery systems, and the targeting efficiency of BNs on some specific targeting receptors for cancer therapy. Furthermore, the review briefly recaps the nanocarrier-based targeted approaches in cancer PDT.